Waterfront City dengan Pendekatan Arsitektur Berkelanjutan Di Kota Parepare - Kurnia, Elvira Dewi; A’raaf Tauhid, Fahmyddin; Rahayu, Irma (TIMPALAJA : Architecture Student Journals, 2023)
Pare-Pare City or commonly referred to as "Pare-Pare Harbor City" is the second-largest city in SouthSulawesi Province which is located on the west coast of Sulawesi Island and has 20 percent of its area is acoastal area. Therefore, the coastal area of Pare-Pare City is an area that can be developed so that it canbecome a productive and efficient area. To minimize damage and create a projected area into the future, inthe effort to develop the waterfront city we apply a sustainable architectural approach to the circulationsystem and use of materials to create a coastal city area with the efficient circulation that is interconnectedin achieving from the city center to the waterfront city and between functions in the area and also the use ofsustainable materials.